2019
DOI: 10.1002/etc.4449
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Beneficial Reuse of Oil and Gas–Derived Produced Water in Agriculture: Physiological and Morphological Responses in Spring Wheat (Triticum aestivum)

Abstract: Produced water (PW) from oil and gas operations is considered a potential resource for food crop irrigation because of increasing water scarcity in dryland agriculture. However, efforts to employ PW for agriculture have been met with limited success. A greenhouse study was performed to evaluate the effects of PW on physiological and morphological traits of spring wheat (Triticum aestivum). Plants were irrigated with water treatments containing 10 and 50% PW (PW10 and PW50, respectively) and compared to a match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…85 Traditionally, bulk organics in conventional PW may also limit both plant health and growth. 86,87 Pica et al recommended a TOC concentration of less than five mg/L to sustain biomass production rates. 88 A number of specific concerns regarding the level of treatment required and the uncertainty associated with PW's impacts on soil health must be resolved prior to widespread use of this resource for agriculture.…”
Section: Nontraditional Sources: Oil and Gas Produced Watermentioning
confidence: 99%
“…85 Traditionally, bulk organics in conventional PW may also limit both plant health and growth. 86,87 Pica et al recommended a TOC concentration of less than five mg/L to sustain biomass production rates. 88 A number of specific concerns regarding the level of treatment required and the uncertainty associated with PW's impacts on soil health must be resolved prior to widespread use of this resource for agriculture.…”
Section: Nontraditional Sources: Oil and Gas Produced Watermentioning
confidence: 99%
“…Experiments simulating a PW spill (Niobrara, CO) on soil concluded that the high salt content of PW can disrupt soil structure and mobilize metal ions like copper, lead, aluminum and manganese during subsequent rainfall events (Oetjen et al, 2018a). Studies on irrigation of wheat with diluted untreated PW not only found reduction in plant development and yield (Sedlacko et al, 2019), but interestingly, a decrease in resistance to pathogens (Miller et al, 2019). Results of these studies indicate that factors beyond the salinity of PW, specifically concentrations of boron (salts of boron are added as crosslinkers) and nature of organic carbon, may play a major role in crop health and therefore must also be considered while determining the level of PW treatment necessary prior to use for irrigation.…”
Section: Salts Radionuclides and Other Ionsmentioning
confidence: 99%
“…A large concurrent study found that irrigation with PW leads to physiological changes and reduced yields in wheat . As a part of this study, we posed an additional and unique question: can water quality impact plant immune response?…”
Section: Introductionmentioning
confidence: 98%
“…Crop yield reduction due to pathogens result in millions of dollars lost per year, even with extensive pesticide use, thus further loss due to irrigation water quality would be problematic. To date, studies focused on the potential reuse of PW for agricultural irrigation have been human-health or plant-yield focused. , The immune response of crops irrigated with O&G PW and then subsequently infected with pathogens is, to our knowledge, unknown. If minimally treated PW proves to be a sustainable, inexpensive, and safe method of crop irrigation, it could be mutually beneficial to farmers in semiarid environments and to O&G companies.…”
Section: Introductionmentioning
confidence: 99%